KONTRIBUSI STUDENTS SENSE OF BELONGING, ACADEMIC SELF EFFICACY DAN HELP-SEEKING TERHADAP PENYESUAIAN AKADEMIK MAHASISWA RANTAU PTN DI BANDUNG - Jesika Rizky Ananda, - (2017)
Penelitian ini bertujuan untuk menguji kontribusi terbesar antara students sense of belonging, academic self efficacy dan help-seeking terhadap penyesuaian akademik mahasiswa rantau PTN di Bandung. Metode penelitian yang digunakan adalah metode kuantitatif dengan sampel penelitian berjumlah 300 responden mahasiswa rantau angkatan 2016 yang berasal dari Universitas Pendidikan Indonesia (UPI), Universitas Padjajaran (UNPAD), Institut Teknologi Bandung (ITB), dan Universitas Islam Negeri Sunan Gunung Djati (UIN SGD). Instrumen terdiri atas Psychological Sense of School Membership Scale (PSSM), College Academic Self-Efficacy Scale (CASES), Help Seeking Scale dan Academic Adjustment Subscale of Student Adjustment to College Questionnaire yang telah diterjemahkan ke dalam Bahasa Indonesia. Analisis data dilakukan dengan menggunakan teknik Multiple Regression Analysis (MRA). Hasil yang diperoleh menunjukkan terdapat pengaruh students sense of belonging, academic self efficacy, dan help seeking terhadap tingginya penyesuaian akademik mahasiswa rantau, baik secara terpisah maupun bersama-sama. ---- This research aims to examine the greatest contribution between students sense of belonging, academic self-efficacy and help seeking assistance to academic adjustment OVERSEAS students of Public Universities or PTN (Perguruan Tinggi Negeri) in Bandung. The research method used is quantitative method with research sample which is used by 300 respondents from overseas students of 2016, it is coming from Universitas Pendidikan Indonesia (UPI), Universitas Padjadjaran (UNPAD), Institut Teknologi Bandung (ITB), and Universitas Islam Negeri Sunan Gunung Djati (UIN SGD). The Instruments consists of the School Membership Scale (PSSM), Academic Self-Efficacy Scale, Help Seeking and Adjustment Subscale of Students Adjustment to Higher Education Questionnaires that have been translated into Bahasa Indonesia. The data analysis used is Multiple Regression Analysis (MRA) technique. The results showed that there is influence of students sense of belonging, academic self-efficacy, and help seeking to high academic ajustment of overseas students, either separately or together.